PENERAPAN WEBSITE DESA SEBAGAI MEDIA INFORMASI PENGENALAN POTENSI DESA SUMBEREJA - Salwa Ibnatisna Sya'bana; Yunike Berry; Rusham Rusham (An-Nizam, 2023)
The progress of information technology is closely linked to the digital and informatics fields. It has become an integral part of people's lives, from using mobile phones to accessing the internet with its various features and functions. The impact of information technology is not limited to urban areas, as it has also reached rural areas. For instance, Sumbereja village still uses manual methods to gather information. This situation inspired the author to create a website for Sumbereja village, which would enable the wider community to gain a better understanding of the village through the web. To address this issue, the Real Work Lecture Activities of Islamic University 45 Bekasi proposed a work program. The program aimed to create an "Application of Village Website as a Medium of Information to Introduce the Potential of Sumbereja Village, Pebayuran District." This service activity focused on developing a village profile website, which would serve as the main source of village information. The data collection process involved documentation, surveys, and interviews with village officials to provide comprehensive information. The primary objective of this initiative was to provide information to the community and assist village officials in delivering public services that could be easily accessed by the public.